Strategi Kepemimpinan Kepala Sekolah dan Iklim Organisasi dalam Meningkatkan Disiplin Kerja Guru - Asep Fathurrahman; Ulfah Alawiyah; H. Taufik; Riduwan Riduwan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study explores the principal’s leadership strategies and the role of organizational climate in improving teacher work discipline. Teacher discipline is a crucial element in ensuring instructional quality, professional accountability, and sustainable school performance. A qualitative case study approach was employed to obtain an in-depth understanding of leadership practices implemented in the natural setting of the school. Data were collected through in-depth interviews, participatory observations, and document analysis involving the principal, vice principals, and teachers. The findings reveal that discipline improvement is shaped by exemplary leadership, dialogic communication, continuous coaching, and the application of humanistic regulations supported by moral and social rewards. In addition, a collegial and supportive organizational climate strengthens collective awareness and encourages teachers to comply with professional standards voluntarily. Discipline is therefore constructed not merely through administrative control but through shared values and social interaction. This study contributes to educational leadership literature by providing contextual evidence of how leadership practices interact with organizational environments in shaping teacher behavior. Practically, the findings offer guidance for school leaders in designing participatory and sustainable discipline development strategies.